PERANAN TRANSPORTASI ONLINE DALAM MENINGKATKAN PENDAPATAN EKONOMI RUMAH TANGGA DRIVER CARAKA INDONESIA PUTUSSIBAU KAPUAS HULU PERSPEKTIF EKONOMI ISLAM - Andi Supriandi (Adisam Publisher, 2023)
Putussibau is the city center of Kapuas Hulu Regency, West Kalimantan Province, which is located on the border with Malaysia. As the center of the Regency city, the existence of Putussibau is expected to help improve the economy of its people with various professions and expertise. Along with current developments in technology and information, the use of online pick-up and drop-off services has emerged. Working as an online driver is very helpful in meeting the household economic needs of theUTussibau community as a main job or additional job. Job as an online driver also does not conflict with Islamic teachings. This research uses a qualitative approach with descriptive research type. Data collection techniques using observation, interviews and documentation. Data analysis uses data reduction analysis, data presentation and drawing conclusions. The results of this research show that 1) Working as an online driver can increase household income, which can be seen from their daily income. There is no prohibition against working as an online driver in Islam, in fact Islam recommends that we always work in our spare time. 2) Working as a driver also has obstacles, namely the weather often changes and the application is not yet perfect, so problems and errors often arise which cause drivers to have difficulty getting passenger orders and other services.